PENINGKATAN KUALITAS PRODUKSI UKM MADU MONGSO DI DESA SANGGRAHAN, KECAMATAN GROGOL, KABUPATEN SUKOHARJO - Raden Baskara Katri Anandito; Siswanti Siswanti; Edhi Nurhartadi (LPPM UNS, 2017)
Sanggrahan Village, Grogol District, Sukoharjo Regency is one of the areas that has many home-based processed food industries. Madu mongso is one of the processed food products in this village. Madu mongso is a snack food made from fermented glutinous rice and addition of sugar and coconut milk. Madu mongso is similar to dodol. Problems faced by madu mongso partners are not yet diversifying raw materials, production capacity is still small, packaging not yet appropriate, not yet have p-irt. The solution offered to the local mongso honey processing industry is through the production process of mongso honey introduction technology made from tubers and fruits (cassava, carrots, soursop) in an effort to diversify the products; The introduction of appropriate technology for the processing of honey mongso in the form of mixing machine; The introduction of various technologies of packaging materials; Home industry food permit (p-irt); And IT-based marketing training and direct selling strategies. In addition, the team has also provided equipment to improve the quality and production capacity of mongso honey mixers and heating, as well as packaging tools that can be used by to support the packaging process.Key words: domestic industry, madu mongso, glutinous rice, quality, diversification